Morpho-Molecular Characterization of Endophytic Fungi From Three Traditional Medicinal Plants - Maria, Zimatul; Shamsi, Shamim; Hosen, Sarowar; Bashar, Md Abul (Bangladesh Journal of Botany, 2024)
The present study focuses on the occurrence of endophytic fungi harboured in the healthy tissues of the three medicinal plants, namely, Adhatoda vasica Nees, Cassia alata L., and Ocimum sanctum L., during the monsoon and winter seasons. Using the "Tissue Planting" method, 19 endophytic fungi were isolated from the leaves and stem of those plants and subsequently identified through morphological characteristics and molecular approaches. From all plants employed in this investigation, Aspergillus flavus, A. niger (Type I), A. niger (Type II), A. terreus, Colletotrichum sp., Penicillium sp.1, Pestalotiopsis mangiferae, and white sterile mycelium were isolated. To delve deeper, ten of these isolates underwent characterization via internal transcribed spacer (ITS) region amplification, and the sequence results obtained utilizing the ITS1 and ITS4 primers were cross-referenced with NCBI GenBank database system through BLAST analysis. The phylogenetic tree generated by the UPGMA method grouped the endophytic fungi into different clades on the basis of genetic distances. Cladosporium xanthochromaticum, Colletotrichum siamense, Fusarium incarnatum, and Talaromyces pinophilus have been recorded for the first time from Bangladesh. The primary findings of this investigation concerning endophytic fungi established a valuable foundation for further research exploring their potential ecological and biotechnological roles in various ecosystems, most importantly in drug discovery. Bangladesh J. Bot. 53(2): 361-372, 2024 (June)